PENGARUH PERIKLANAN DAN FASILITAS TERHADAP KEPUTUSAN MENGINAP DI HOTEL GRAND DAFAM BELA TERNATE (STUDI PADA TAMU YANG MENGINAP DI HOTEL) - Ibnu Sina Hi Jusuf; Laela Laela; Firda Novita Sari (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2018)
This study aims to examine the influence of advertising and facilities on the decision to stay at the grand hotel dafam Bela Ternate. The sample in this study amounted to 65 respondents. The sampling technique uses non probality sampling technique and the data collection technique used is by distributing questionnaires, interviews and observations. Data analysis in this study is using multiple regression analysis. The results of this study indicate that partially the Advertising Variables (X1), Facilities (X2), have a positive and significant effect on the decision to stay and simultaneously or together Advertising Variables (X1), Facilities (X2), influence the decision to stay at the Hotel Grand Dafam Bela Ternate.